Advancing geographic information systems (GIS) and econometric analyses for monitoring natural resources and visitors’ preferences in national parks - Gurung, Bijan (My University, 2025)
The U.S. National Park Service (NPS) and the U.S. National Forest System conserve vast areas of public land in the U.S., including diverse ecological landscapes, and provide space and opportunities for outdoor recreational activities. The NPS and the U.S. Forest Service have been conducting inventory, monitoring, and research to assess specific natural resource conditions and visitor use experiences through direct and indirect monitoring methods. Some key monitoring activities include acoustic monitoring in national parks, low-level overflight monitoring in parks popular for air tours, lightscape pollution monitoring, land use and land cover analysis, vegetation monitoring, endangered species and habitat monitoring, climate change vulnerability assessments, and visitor usage monitoring. Monitoring is an important component of evidence-based decision-making in parks and forests. However, monitoring has been more opportunistic than systematic, and it is challenging to maintain long-term, systematic monitoring of natural resources in parks and forests. Meanwhile, monitoring tools and techniques are constantly evolving through the application of satellite and communication technology, powerful computers, smartphones, and cloud services. New monitoring tools and techniques have made data collection more efficient and effective, often capturing information from remote areas of the landscape using satellite and radio signals. This dissertation comprised three discrete studies on monitoring natural resources and visitors’ preferences in national parks and forests. The first study estimated the acoustic active space from two aircraft categories in the Cades Cove site of the Great Smoky Mountains National Park (GRSM) using newer technology. The NPS-ActiveSpace toolkit, an open-source software developed by the NPS, was employed to pair overflight and acoustic data of aircraft recorded by the Automatic Dependent Surveillance-Broadcast (ADS-B) data logger and a sound level meter (SLM), respectively, in 2023. The jet aircraft (fixed-wing multi-engine) were parsed into two categories based on their maximum takeoff weight: “Light” with a takeoff weight less than 20,000 pounds, and “Heavy” with a takeoff weight more than 20,000 pounds. “Heavy” aircraft generated a larger active space than “Light” aircraft. The second study investigated low-level aircraft data recorded by two flight monitoring systems—the ADS-B data logger and onboard GPS—in Denali National Park and Preserve (DENA) from 2021 to 2023. DENA is popular for air tours and air taxi services for tourists, mountaineers, and backcountry users. The two systems were compared by analyzing their geospatial data characteristics, specifically their waypoint locations across x, y, and z dimensions. The ADS-B and onboard GPS datasets were compared based on the length of the overflights, spatial coverage of waypoints, and altitude discrepancies. The results demonstrated that onboard GPS was more effective for overflight monitoring in the rugged, mountainous terrain of DENA. The third study examined visitors’ preferences for alternative recreation sites during wildfire- and drought-induced displacement using a discrete choice experiment in the national forests of Southern California. The questionnaire survey was conducted in the summer of 2024 at eight priority sites across four national forests. Conditional logit models were applied to analyze respondents’ preferences for site attributes. The models showed preferences for “wildland-urban” views and “wildlands” views compared to “city” views in the wildfire-induced displacement scenario, whereas “1–2 hours” and “>2 hours” of travel time compared to “less than 1 hour” travel time in the drought-induced displacement scenario. Additionally, variations in preferences across socio-demographic groups were analyzed to understand preference heterogeneity within the population. The findings of these three discrete studies will assist park and forest managers in several ways, including mapping aircraft routes and noise, determining the most effective technologies for aircraft tracking over national parks, and identifying the preferences for site attributes and environmental factors during recreation displacement in Southern California national forests. These efforts will advance monitoring tools and techniques while supporting natural resource conservation and meeting the recreational and educational needs of a growing population.
Advancing geographic information systems (GIS) and econometric analyses for monitoring natural resources and visitors’ preferences in national parks and forests
Keywords: Aircraft noise; Active space; Automatic dependent surveillance-broadcast (ADS-B); Onboard GPS; Discrete choice experiment; Recreation displacement